Uma perspectiva trágica do sofrimento nas práticas escolares - Seibert, Deisi Mônica (Universidade do Vale do Rio dos Sinos, 2019)
This investigation aims to analyze how suffering has been operated in school practices with children from the early years of a public school in São Leopoldo. So, the theory is mainly based on the Nietzschean perspective of the tragic concept to discuss the imperative that relates happiness and childhood. In addition to this concept, which guides all research, others are used to compose this study, such as philosophy with children, “childhood of thought” and great health. Besides Nietzsche, other authors theorize this conversation, such as Deleuze, Lopez, Kohan, Larrosa, Kastrup, Corazza, Nikolay, among others. Thus, philosophical workshops were developed with teachers and students from the third years of elementary school as a more intensive way of doing research in education. The strength of the statement of caring was observed at the workshops, opening up to three dimensions of “gene-carto-logic” analysis: salvation that imprisons, caring and teaching responsibility; and presence-absence, life-death. Hence, school is understood as this struggle of forces, marked by a salvationist logic, but still constituting itself as an important space of reception and exercise of thought about childhood, suffering, life and death. Thus, I propose, “despite care", which contemplate this tragic view of suffering.
Keywords: Infância; Escola; Sofrimento; Trágico; Oficinas de Filosofia com crianças; Childhood; School; Suffering; Tragic; Philosophy with children workshops; ACCNPQ::Ciências Humanas::Educação